GAMBARAN KUALITAS HIDUP PASIEN CHRONIC KIDNEY DISEASE (CKD) YANG MENJALANI HEMODIALISA DI RS GRHA KEDOYA JAKARTA BARAT TAHUN 2024 - Ramadani, Putri; Suminar, Mira; Ernawilis (Jurnal Kesehatan STIKes IMC Bintaro, 2024)
Introduction: The kidneys are organs that play an important role in maintaining environmental stability in the body and the survival and normal function of cells depends on maintaining the concentration of salts, acids and electrolytes. Research Objective: To determine the description of the quality of life in chronic kidney disease (CKD) patients undergoing hemodialysis (HD) at Grha Kedoya Hospital, West Jakarta in 2024. The research method uses the Quota Sampling method or technique. The analysis technique uses the Chi-square test, which is a statistical test used to test the significance of two variables. The research results of the p-value are that the majority of respondents aged 46-55 years 30 (38.5%), male 52 (66.7%), last education Academy/PT 31 (39.8%), long undergoing HD for less than 2 years 51 (65.4%), the person who cared for them during their illness was a relative 40 (51.3%), the illness they experienced was 2-3, namely 39 (50.0) eGFR value 78 (100.0 %). In addition, 57 patients (73.1%) had comorbid hypertension, 59 patients (75.6%) had comorbid heart disease, 55 patients (70.5%) had diabetes mellitus and 47 patients (60.3%) had comorbid hyperlipidemia and The results of the analysis also show the number of comorbid hemodialysis patients in the Hemodialysis Unit of Grha Kedoya Hospital, West Jakarta. It is known that 15 patients (19.2%) had 1 comorbidity and 63 patients (80.8%) had > 1 comorbidity. Of the 78 respondents, 49 (62.8%) had good physical health, 49 (62.8%) had good psychosis, 43 (55.1%) had good social relations and 53 (67.9%) had a good environment. Recommendation: The results of this research are expected to improve and enrich geriatrics knowledge, especially in therapeutic communication, increased empathy in service and occupational therapy and become additional knowledge for nurses in increasing their ability to provide professional nursing care, especially for patients undergoing hemodialysis and become a reference for future researchers Keywords: Quality of Life,Hemodialysis